End-to-End Procurement Architecture from Requisition to Analytics (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
Denny's and CSCS (in conjunction with HAVI) deployed a cloud-based Source-to-Pay (S2P) solution powered by Ivalua for all 3400 restaurants within 15 months to reduce the risk of supply chain disruptions having a major financial impact on Denny's restaurant operations. The approach of employing a phased rollout led to savings of 18%, equating to $12 million in costs for each year of the project's duration additionally, it allowed for a number of major achievements such as provision of a digital procurement framework, created over multiple older systems. There were also great efficiencies realized through the projects execution due to a 92% first-time match rate and the ability to complete procurement cycles within only 72 hours as opposed to 45 days. Technical innovations achieved included real-time connectivity with SAP/EDW, creation of custom ticketing solutions, creation of analytical reports to deliver information through multiple dashboards used for transaction monitoring. The project established the benefits delivered through the phased approach to deployment, reduced risk to an organization due to implementation decisions and demonstrated the importance of AI-ready cloud architecture for rapid procurement agility. Movement forward will continue by incorporating blockchain, Internet of Things monitoring and generative AI will further expand and enhance savings and position Denny's / CSCS as a leader in digitalizing food service procurement.
Keywords: Source-to-Pay (S2P); Supply Chain Disruptions; Digital Procurement Framework; Blockchain; Internet of Things.